2021
DOI: 10.13040/ijpsr.0975-8232.12(8).4167-73
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Traditionally Persea schiedeana is used for headache relief, as anti-hypertensive, nervous relaxant, dermal diseases, among others. In this study, this plant from Salvadorian flora acute toxicity was evaluated in-vivo at 500 mg/kg, and the analgesic activity was tested by acetic acid, formalin, and tail flick tests in NIH Swiss mice at doses of 100, 250, and 500 mg/kg body weight, using as a positive control Indomethacin 10 mg/kg and distilled water as a control. Secondary metabolite profile was performed by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Persea schiedeana Nees’s case has not been analyzed still as a corrosion inhibitor alternative. Even so, a few analyses were done by some authors, reporting that its chemical compositions found the presence of Fatty acids such as Oleic acid and Palmitic acid, as phenolic and antioxidant activities had been reported 12 14 . Then, most studies have been conducted to evaluate the nutritional value of the PSN or its agro-industrial potential to increase its production 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Persea schiedeana Nees’s case has not been analyzed still as a corrosion inhibitor alternative. Even so, a few analyses were done by some authors, reporting that its chemical compositions found the presence of Fatty acids such as Oleic acid and Palmitic acid, as phenolic and antioxidant activities had been reported 12 14 . Then, most studies have been conducted to evaluate the nutritional value of the PSN or its agro-industrial potential to increase its production 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Persea schiedeana Nees´s case has not been analyzed still as a corrosion inhibitor alternative. Even so, a few analyses were done by some authors, reporting that its chemical compositions found the presence of Fatty acids such as Oleic acid and Palmitic acid, also phenolic and antioxidant activities had been reported [12][13][14].…”
Section: Introductionmentioning
confidence: 99%